Complication on Premature Rupture of Membrane in Intrapartum Mother Infected with COVID-19: Meta-Analysis - Hepti Widia Ningsih; Bhisma Murti; Uki Retno Budihastuti (Masters Program in Public Health, 2022)
Background: Pregnant women and fetuses are populations that are at high risk of being infected with the virus. COVID-19 in pregnant women is considered a risk factor for causing complications in pregnancy such as premature rupture of membranes. This study aims to analyze complications of premature rupture of membranes in mothers infected with COVID-19.Subjects and Method: This was a systematic review and meta-analysis. Article searches were conducted using electronic databases such as Google Scholar, PubMed and Science Direct. The articles used are articles published from 2020-2022. Keywords to search for articles were: “COVID-19” OR “2019-nCoV” OR “novel coronavirus” OR “SARS-CoV-2” OR “coronavirus 2” AND “premature rupture of membrane” OR “prelabour rupture of membrane” AND “pregnancy.” The inclusion criteria used were full text articles in English with a cohort study design, multivariate analysis with Adjusted Odds Ratios (aOR), research subjects were pregnant women, intervention was COVID-19 infection, comparison was not infected with COVID-19 , the outcome of the study was premature rupture of membranes.The results of the search for articles were included in the PRISMA diagram and analyzed using the Review Manager 5.3 application.Results: A total of 9 cohort study articles from the United States, Bangladesh, China, India, Mexico, Romania, and Spain were selected for systematic review and meta-analysis. The results showed that pregnant women infected with COVID-19 had a risk of complications of premature rupture of membranes as much as 2.26 times compared to pregnant women who were not infected with COVID-19 and the results were statistically significant (aOR = 2.26; 95% CI = 1.33 to 3.82; p = 0.002).Conclusion: Pregnant women infected with COVID-19 increase the risk of premature rupture of membranes. Keywords: COVID-19, pregnancy, premature rupture of membranes, meta-analysis Correspondence:Hepti Widia Ningsih. Masters Program in Public Health Universitas Sebelas Maret, Jl. Ir, Sutami 36A, Surakarta 51726, Central Java. Email: heptiwidian@gmail.com. Mobile +6285729442615.